Tracking Infection and Genetic Divergence of Methicillin-Resistant Staphylococcus aureus at Pets, Pet Owners, and Environment Interface - Shoaib, Muhammad; Aqib, Amjad Islam; Ali, Muhammad Muddassir; Ijaz, Muhammad; Sattar, Huma; Ghaffar, Awais; Sajid Hasni, Muhammad; Bhutta, Zeeshan Ahmad; Ashfaq, Khurram; Kulyar, Muhammad Fakhar-e-Alam; Pu, Wanxia (Frontiers in Veterinary Science, 2022)
Staphylococcus aureus (S. aureus) has become a leading animal and public health pathogen that keeps on transferring from one host to other, giving rise to newer strains by genetic shifts. The current study was designed to investigate the epidemiology and genetic relatedness of mecA gene in S. aureus isolated from pets, immediate individuals in contact with pets, and veterinary clinic environments. A total of n = 300 samples were collected from different veterinary hospitals in Pakistan using convenience sampling. The collected samples were subjected to microbiological and biochemical examination for the isolation of S. aureus. Methicillin resistance was investigated by both phenotypically using oxacillin disk diffusion assay and by genotypically targeting mecA gene by PCR. PCR amplicons were subjected for sequencing by Sanger method of sequencing, which were subsequently submitted to NCBI GenBank under the accession numbers MT874770, MT874771, and MT874772. Sequence evolutionary analysis and mecA gene characterization was done using various bioinformatics tools. Overall, 33.66% mecA genes harboring S. aureus strains were isolated from all sources (33.33% from pets, 46.0% from surrounding, and 28.0% from immediate contact individuals). The bioinformatics analysis noted that one SNP was identified at position c.253C>A (Transvertion). The phylogenetic tree (two clades) of S. aureus mecA revealed a possibility of inter-transmission of disease between the environment and pets. Frequency of adenine and thymine nucleotide in motifs were found to be the same (0.334). Cytosine and guanine frequency were also the same (0.166). Threonine was replaced by asparagine (p.T84D) in each sample of cat, environment, and human. On the other hand, protein structures ofcat-1 and cat-2 proteins were found identical while cat-3, environmental, and human proteins shared identical structures. The study thus concludes rising circulation of methicillin-resistant S. aureus (MRSA) strains in animal-human-environment interfaces, forecasting the development of novel strains withmodified range of resistance.